TOLERANCE: ITS CONCEPT AND FOUNDATIONS IN ISLAM - Benazouaou Amar (International Journal of Innovative Technologies in Social Science, 2025)
Undeniably, Islam has promoted a message of tolerance and openness from the very beginning of its mission—within structured frameworks that ensure peaceful coexistence and harmony. Its timeless teachings—from the Qur’an and the Prophet’s (s) sayings to its rich intellectual heritage—are replete with examples of this ethos. The profound and continued influence of this faith from its inception to the present day underscores that Islam at its core is a call to peace, tolerance, universalism, and communal living (global citizenship), based on mutual respect, genuine engagement, and the rejection of all forms of violence and extremism. This scholarly summary provides an epistemological foundation, clearly demonstrating that Islam has long embraced the concept of tolerance and actively encourages acceptance of the other. It illuminates the true meaning of tolerance in Islam.